2005
DOI: 10.5858/2005-129-96-alltia
|View full text |Cite
|
Sign up to set email alerts
|

Acute Lymphoblastic Leukemic Transformation in a Patient With Chronic Idiopathic Myelofibrosis and Paroxysmal Nocturnal Hemoglobinuria: A Case Report and Review of the Literature

Abstract: Leukemic transformation of chronic idiopathic myelofibrosis (CIMF) to acute lymphoblastic leukemia (ALL) is rare. We report a case of a patient with CIMF who developed paroxysmal nocturnal hemoglobinuria (PNH) 2 years after initial presentation. His disease eventually transformed to ALL of precursor B-cell type. In that CIMF and PNH are clonal stem cell disorders with different pathogeneses, there may be an association between them. However, leukemic transformation is a rare sequel of both disorders. Coexisten… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 14 publications
0
9
0
1
Order By: Relevance
“…Although none of them developed classic hemolytic PNH, we demonstrated the persistency of PNH clones in 88% of the 26 cases that had been tested at least twice. Some Authors described the occurrence of PNH clones in MPN [ 13 15 ], and Fraiman et al reported one patient developing a PNH clone of 60% on granulocytes and hypothesized the cooperation with CALR driver mutation in PNH clone selection and expansion [ 14 ]. Similar data were recently confirmed by Richards et al in five patients with MPN that mainly showed association of PIG-A mutation and JAK2 V617F or other MPN driver mutations [ 13 ].…”
Section: Discussionmentioning
confidence: 99%
“…Although none of them developed classic hemolytic PNH, we demonstrated the persistency of PNH clones in 88% of the 26 cases that had been tested at least twice. Some Authors described the occurrence of PNH clones in MPN [ 13 15 ], and Fraiman et al reported one patient developing a PNH clone of 60% on granulocytes and hypothesized the cooperation with CALR driver mutation in PNH clone selection and expansion [ 14 ]. Similar data were recently confirmed by Richards et al in five patients with MPN that mainly showed association of PIG-A mutation and JAK2 V617F or other MPN driver mutations [ 13 ].…”
Section: Discussionmentioning
confidence: 99%
“…In PNH, acquiring additional MPN-associated gene mutations might promote clonal expansion of the PIGA mutant clone, consequently inducing clinical manifestation of both MPN and PNH [27]. Interestingly, a few cases of coexistence of PMF and PNH have been reported (Table 2) [11,12,14,16]. One recent study reported that PNH clones were found in 2% of MPN patients [15].…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, a few cases of coexistence of PMF and PNH have been reported ( Table 2 ) [ 11 , 12 , 14 , 16 ]. One recent study reported that PNH clones were found in 2% of MPN patients [ 15 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations